2007
DOI: 10.1152/ajpendo.00394.2007
|View full text |Cite
|
Sign up to set email alerts
|

Glyceroneogenesis and the supply of glycerol-3-phosphate for glyceride-glycerol synthesis in liver slices of fasted and diabetic rats

Abstract: The pathways of glycerol-3-phosphate (G3P) generation for glyceride synthesis were examined in precision-cut liver slices of fasted and diabetic rats. The incorporation of 5 mM [U-(14)C]glucose into glyceride-glycerol, used to evaluate G3P generation via glycolysis, was reduced by approximately 26-36% in liver slices of fasted and diabetic rats. The glycolytic flux was reduced by approximately 60% in both groups. The incorporation of 1.0 mM [2-(14)C]pyruvate into glyceride-glycerol (glyceroneogenesis) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…4). Previous in vitro experiments have shown that a reduction in the G3P generation via glycolysis is accompanied by a significant activation of glyceroneogenesis in liver slices during fasting [11]. We have also previously demonstrated in vitro that G3P synthesis from glucose is increased and glyceroneogenesis is reduced in IBAT from cafeteria-diet-fed rats [9].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…4). Previous in vitro experiments have shown that a reduction in the G3P generation via glycolysis is accompanied by a significant activation of glyceroneogenesis in liver slices during fasting [11]. We have also previously demonstrated in vitro that G3P synthesis from glucose is increased and glyceroneogenesis is reduced in IBAT from cafeteria-diet-fed rats [9].…”
Section: Discussionsupporting
confidence: 66%
“…1 Sources and pathways of glycerol-3-phosphate generation in adipose tissue and the liver and possible systemic recycling of fatty acids medium, respectively; both pathways are increased in the liver from fasted and diabetic rats [11]. In both situations, the glycolytic flux (estimated by the amount of 3 H recovered from water after incubation of liver slices in medium containing 3 H-glucose) and the generation of G3P from glucose (assayed by the rate of 14 C-glucose incorporation into glyceride-glycerol) are reduced in the liver slices [11]. These primarily in vitro findings from WAT, BAT and liver suggest that glyceroneogenesis and glycolysis would be reciprocally regulated to ensure the generation of G3P that is necessary for FA esterification and TAG synthesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced hepatic de novo lipogenesis, as a result of reduced SREBP-1c and FAS, could indeed participate in reduced VLDL production and storage of TG inside adipocytes, thereby reducing adiposity. Regarding liver glyceroneogenesis, it was estimated by Martins-Santos et al (33) that it would contribute to only 20% of the G3P generated for TG synthesis in the liver of fasted rats. To evaluate that point in our mice, we compared pyruvate incorporation into the liver of fasted WT and ROR sg/sg mice (n ϭ 4).…”
Section: Discussionmentioning
confidence: 99%